Understanding the Interplay of Psychological and Social Factors in Juvenile Delinquency: Implications for Intervention and Prevention Strategies - Purga, Albert; Oktavia, Gisella Putri (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
Juvenile delinquency presents a multifaceted societal concern, marked by unlawful behaviors among adolescents. This research delves into the intricate relationships between psychological and social factors, seeking to unravel their collective influence on delinquent behaviors among youth. Employing a mixed-method approach, this study investigates the correlations between psychological vulnerabilities such as impulsivity, trauma, and mental health indicators and social dynamics including family environments, peer influences, and socio-economic disparities. Findings reveal statistically significant associations between psychological factors and delinquency, with impulsivity and unresolved trauma demonstrating robust correlations. Social factors, notably family dynamics and peer influence, emerge as influential determinants of delinquent behaviors. Moreover, the study unveils the interplay between these factors, emphasizing their combined impact on juvenile delinquency. The implications drawn from this research underscore the necessity for holistic interventions that encompass mental health support, family interventions, peer education, and community-based programs. Collaborative efforts among stakeholders and the implementation of evidence-based strategies are crucial in addressing delinquency effectively.